Code implementation of particle based discrete element method for concrete viscoelastic modelling - Serra, C. (2015)
This report describes the application of discrete element method to rigid particle models and proposes the use of the discrete element method for the modelling of the behaviour of concrete, namely the time-independent and time-dependent or instantaneous and delayed behaviour. The main goals of this work are: i) the implementation of a discrete element method code using rigid particles; and ii) the implementation of constitutive contact models for the delayed behaviour of concrete. Elastic, viscoelastic and aging models were implemented and several examples were used to validate the method. A fast numerical simulation scheme for the creep behaviour was applied to decrease the computational effort over large loading times for the analysis of concrete behaviour.